Contemporary art in the Federal Republic of Germany : 12 collections of 30 graphics : Script and Image. - Adriani, Götz (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1979)
Bayrle, Thomas ; Biel, Michael von ; Brüning, Peter ; Burkhardt, Klaus ; Cremer, Siegfried ; Darboven, Hanne ; Kriwet, Ferdinand ; Mayer, Hans-Jörg ; Mitzka, Ernst ; Reichert, Josua ; Roehr, Peter ; Roth, Dieter ; Ulrichs, Timm ; Wewerka, Stefan
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland